Geography, (M)Other Tongues and the Role of Translation in Giannina Braschi's El imperio de los sueños - María M. Carrión (Studies in 20th & 21st Century Literature, 1996)
The Big Apple seems to be the central axis for the readerly and writerly "I" in El imperio de los sueños (Empire of Dreams), by Giannina Braschi. Readers can easily realize that the text is not just about New York, but that it actually journeys through praise and blame, drinking and dancing, talking and perversing many other cities and landscapes. El imperio is a space of bohemia with streaks from the Latin American Quarter in Paris, the barrio chino barcelonés, the zaguanes of Borges's Buenos Aires, from colonial houses in Old San Juan; it evokes dandy places, the Madrid of the Profane Comedy, also, of course, an Empire State full of shepherds and other poetic voices. This textual geography, intertwined with socio-political maps and blueprints of different cultural systems and manners, leads to a boiling pot of literary references. In sync with its new maps of New York, Russia, Puerto Rico, Spain, and Latin America, El imperio represents Spanish as a strong and vivid character chiseled after many national and communal forms and frames of meaning; nothing along the lines of a preformulated vehicle for Braschi's narrative and/or poetic acts. The text displays an endless mix-and-match of Puerto Rican idioms—both from the Island and from the Spanish spoken in New York by Puerto Ricans—with expañolismos, argentinismos, and other renditions of Spanish. The tongue of Spain, the madre patria, thus multiplies its performative potential and expands the role of translation. In El imperio Spanish is not just a process to move meanings beyond its lettered confinements, out of its "grammatically correct" boundaries, into another—or foreign—language, but a way to show off its own capacity for otherness.
Keywords: El imperio de los sueños; Giannina Braschi; Puerto Rican literature; New York; journey; landscape; space; barrio chino barcelonés; zarguanes; Borges; Old San Juan; Profane Comedy; Madarid; geography; textual geography; nation; nationalism; identity; boundaries; other; otherness